Gênero e políticas públicas: o atendimento a mulheres vítimas de violência no município de Guarapuava (PR) - Pienegonda, Fernanda Keli (2018)
ABSTRACT This study aims at discussing about how public policies have assisted women victims of violence in Guarapuava city, Paraná. It is a qualitative approach, which sought to understand such practices guided by participative research method, whereby researcher attended monthly meetings from February to December in 2017, and these meetings have been led by Network for Addressing Violence against Women, situated in Guarapuava-PR. Even to collect data, one administered a questionnaire asking professionals that work at the mentioned group, what are their perceptions concerning the public policies for women in the city. Fourteen professionals from different occupations and sectors such as psychology, social service, nursing, military and civilian polices, among others attended this step. Thus, following thesis is divided into three chapters. First chapter presents main national public policies related to addressing violence against women and specialized police station, a concise review about Brazilian Maria da Penha Law, conceptualization of service networks, and some information about Paraná state, as well as services statewide. Second chapter presents information related to the Guarapuava city in respect of the public policies history dedicated for women, likewise about Secretariat of Policies for Women and its actions, and how are articulated the ones Network for Addressing has taken. In the third chapter, the corpus composed of data collected with professionals above mentioned is provided and discussed, in order to understand how Guarapuava city has managed services, by means of a questionnaire about professionals. training and perception on such services. Another important aspect in this section is the discussion about building subjectivities. On this view, participative research was crucial to realize in what way network took form in ordinary meetings of Network for Addressing Violence in Guarapuava city, PR. Based on this study, it is possible to notice that implementation of Public Policies for Women is recent, but an important turning point in the local politics. Therefore, one highlights the creation of Secretariat of Policies for Women and its actions in the city, bearing in mind articulation that occurs with national public policies and service networks to indispensable discussions, and consequently, promoting achievement of public policies goals. Professionals that composed service networks were engaged into their work, and they acknowledged technical skills are quite important. These professional point out lack of human resources and emphasize that physical structure is precarious concerning to the public services offered in the city, which raise low investment and a far view on this issue.